2017
DOI: 10.1021/jacs.7b07487
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Unique Catalytic Performance of Silyl-Group-Substituted Geminal Dichromiomethane Complexes Stabilized with a Diamine Ligand

Abstract: Stabilization by a silyl group on the methylene carbon and a diamine ligand led to the isolation of gem-dichromiomethane species. X-ray crystallography confirmed the identity of the structure of this rare example of reactive gem-dimetalloalkane species. The isolated gem-dichromiomethane complex acted as a storable silylmethylidene carbene equivalent, with reactivity that could be changed dramatically upon addition of a Lewis acid (ZnCl) and a base (TMEDA) to promote both silylalkylidenation of polar aldehydes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 83 publications
2
24
0
Order By: Relevance
“…Our preliminary result for borylcyclopropanation was reported in 2007, in which two terminal alkenes (allyl benzyl ether and 1-dodecene) were demonstrated as substrates with I 2 CHBpin prepared in situ from the reaction of Cl 2 CHBpin and LiI, resulting in low stereoselectivity (up to 63:37) . During a detailed study to clarify the reactive chromium species and reaction mechanism, Charette and co-workers recently reported Simmons–Smith type borylcyclopropanation of olefins using a borylmethylzinc carbenoid (Scheme , eq 2) . As exemplified by this report, olefin substrates for most of the previously reported stereoselective cyclopropanation are limited to allylic ethers and aryl olefins .…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Our preliminary result for borylcyclopropanation was reported in 2007, in which two terminal alkenes (allyl benzyl ether and 1-dodecene) were demonstrated as substrates with I 2 CHBpin prepared in situ from the reaction of Cl 2 CHBpin and LiI, resulting in low stereoselectivity (up to 63:37) . During a detailed study to clarify the reactive chromium species and reaction mechanism, Charette and co-workers recently reported Simmons–Smith type borylcyclopropanation of olefins using a borylmethylzinc carbenoid (Scheme , eq 2) . As exemplified by this report, olefin substrates for most of the previously reported stereoselective cyclopropanation are limited to allylic ethers and aryl olefins .…”
mentioning
confidence: 90%
“…We focused on the early transition metals as promoters, and developed chromium-mediated selective cyclopropanation of unactivated terminal alkenes (Scheme , eq 1). , This method provided cyclopropanes containing synthetically useful iodo and silyl , functionality in a single step from commercially available terminal alkenes. Recently, our mechanistic studies indicated that the reaction proceeded via generation of a gem -dichromiomethane (Cr–CHR–Cr) as a key reactive species from diiodomethane derivatives. , We envisioned that the use of diiodomethylboronate esters would provide borylcyclopropanes that could be utilized as efficient building blocks to incorporate a cyclopropyl ring into the target molecules through the Suzuki–Miyaura cross-coupling reaction . Several methods for providing borylcyclopropanes have been reported, including cyclopropanation of alkenylboranes with metal carbenoids, hydroboration of cyclopropenes, direct borylation of cyclopropanes having heteroatom-containing directing groups, and cross-coupling reactions with cyclopropyl halides .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of such “Schrock”-type nucleophilic carbenes and their applicability/superb performance in fundamental organic transformations such as olefin metathesis and carbonyl methylenation (Wittig-type reactivity) , have triggered immense research activities. ,, Tebbe’s compound Cp 2 Ti­(μ-CH 2 )­(μ-Cl)­Al­(CH 3 ) 2 , also termed the Tebbe reagent, involving a Lewis acid (LA = AlMe 2 Cl) stabilized [TiCH 2 ] moiety, , has featured a most efficient (rapid CO to CCH 2 conversion at ambient temperatures) and hence prominent carbonyl methylenation reagent in organic synthesis ever since. Crucially, in natural product synthesis the Tebbe reagent often outperforms the Wittig reagent CH 2 PPh 3 due to its enhanced functional group tolerance (e.g., ester or acetal) and also the Petasis reagent Cp 2 Ti­(CH 3 ) 2 , which requires elevated temperatures (65 °C) to form the [TiCH 2 ] moiety via methane elimination. Drawbacks of the Tebbe reagent are its moisture sensitivity, the coformation of Ti­(III) species when Cp 2 TiCl 2 is reacted with the “reducing” reagent AlMe 3 , and the viability of only methylenation. , On the other hand, reduced titanium species such as those obtained from the ternary systems CH 2 Br 2 /TiCl 4 /Zn and CH 2 Br 2 /TiCl 4 /Mg have been employed according to the Takai–Lombardo reaction for the mild methylenation of ketones counteracting enolization (thus counteracting any epimerization of α-chiral centers; also displaying high functional group tolerance). , Moreover, an excess of divalent Cp 2 Ti­[P­(OEt) 3 ] 2 (via Cp 2 TiCl 2 /Mg/P­(OEt) 3 ) has been successfully used in the olefination of thioacetals with carbonyl compounds (Takeda reaction, also characterized by a wide substrate scope) . Switching to group 6 reagents, the iodo-methylidene Cr­(III) complex Cr 2 Cl 4 (CHI)­(THF) 4 (Takai olefination reagent) has been employed successfully to convert aldehydes to E -iodido-functionalized olefins accessible to further derivatization. …”
Section: Introductionmentioning
confidence: 99%
“…Bench-stable gem -dimetalloalkanes (R 2 CM 1 M 2 ) possessing two metal atoms on the same carbon are classical but still important reagents in organic synthesis , Thanks to their mild reactivity, functional groups on the gem -dichromiomethane species were well-tolerated to convert various aldehydes into synthetically useful alkenyl iodides, silanes, and boranes with high regioselectivity . In addition, we have reported that proper Lewis base additives could change the reactivity of gem -dichromiomethane species as chromacarbene equivalents to promote cyclopropanation of unactivated alkenes (Figure (a)). , While the reactivity of gem -dimetallomethanes with double bonds of both polar CO and nonpolar CC have been studied, their use for the transformation of a triple bond of alkynyl CC is severely limited .…”
mentioning
confidence: 99%